Absorptive capacity and product innovation: new evidence from Nigeria. Issue 2 (2nd July 2016) - Ukpabio, M. G.; Adeyeye, A. D.; Oluwatope, O. B.
ABSTRACT: This paper assesses the influence of absorptive capacity (AC) on firms' product innovation by relying on pooled cross-sectional data from innovation surveys among Nigerian manufacturing and service firms. The study employs variables such as educational qualification, technology acquisition, intramural R&D and collaboration as proxies for measuring AC. Using the ordinal logit model, our result shows that higher educational qualification is the determinant of product innovation among manufacturing firms while collaboration with knowledge institutions, the determinant among service firms. In addition, the impact of R&D investments on product innovation becomes significant among manufacturing firms when moderated with age. We can thus infer that high-level skilled workers and external collaboration increase the likelihood of introducing new-to-market product innovations among manufacturing and service firms respectively by enhancing the AC of firms. Similarly, R&D investment can only have impact on the ability to introduce new-to-market product innovations as firms mature with age. Since the factors of AC driving the two sectors differ, there is therefore no one-cap-fit-all solution. Hence, there is the need for sector-specific policies that will enhance firms' competences and capabilities and drive national competitiveness. These include state interventions through government policy instruments in areas such as education, training, intellectual property and funding among others. Careful consideration should however be made in introducing these interventions in order to avoid government failure.